2019
DOI: 10.1002/mar.21277
|View full text |Cite
|
Sign up to set email alerts
|

The ethical underpinnings of nonmaterialistic values and voluntary simplicity behavior in the United States

Abstract: Many scholars agree overconsumption is a serious ethical problem because of its adverse effects on the environment. This multimethod article uses two studies to explore the ethical underpinnings of two related consumer expressions of anticonsumption: nonmaterialism, which refers to not placing importance on material goods, and voluntary simplicity, which refers to reducing consumption behavior. Study 1 employs Structural Equation Models of secondary U.S. data and finds that nonmaterialism and voluntary simplic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
1
17
0
2
Order By: Relevance
“…Azevedo, 2020 ; Garcia-Ruiz & Rodriguez-Lluesma, 2014 ), while empirical studies have reported mixed support for the influence of ethical ideology on anti-consumption (e.g. Sadbury-Riley et al 2018; Peifer et al, 2020 ) or sustainable/prosocial consumption (Zou & Chan, 2019; Chowdhury, 2018 ). With the introduction of MFT, we supplement the findings of these earlier studies with an alternative morality-related concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azevedo, 2020 ; Garcia-Ruiz & Rodriguez-Lluesma, 2014 ), while empirical studies have reported mixed support for the influence of ethical ideology on anti-consumption (e.g. Sadbury-Riley et al 2018; Peifer et al, 2020 ) or sustainable/prosocial consumption (Zou & Chan, 2019; Chowdhury, 2018 ). With the introduction of MFT, we supplement the findings of these earlier studies with an alternative morality-related concept.…”
Section: Discussionmentioning
confidence: 99%
“…This regulation of self-interest (versus societal interest) is central to morality (Campbell & Winterich, 2018 ). It is therefore not surprising that morality has been identified as a relevant predictor in the domain of anti-consumption (Makri et al, 2020 ), and although this has previously remained on the sidelines of such discussions it has recently been moving to the forefront of scholars’ interest (see Azevedo, 2020 ; García-de-Frutos et al, 2018 ; Muncy & Iyer, 2021 ; Peifer et al, 2020 ; Sudbury-Riley & Kohlbacher, 2018 ). Sekhon and Soule (2019) identified a gap in the literature with regard to the role of contextually relevant consumer characteristics and the motives that people ascribe to anti-consumption, when driven by environmental and not financial reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptual papers 33 Read et al (2018), Buell (2005), Elgin and Mitchell (1977), Alexander (2013), Olsen (1981), Haenfler et al (2012), Connolly and Shaw (2006), Kasser (2009), Etzioni ( 2004), Alexander (2012), Gambrel and Cafaro (2010), Romano (2012), Alexander (2011), Hall (2011, Kronenberg andIida (2011), Garcia-Ruiz andRodriguez-Lluesma (2014), Librova (2008), Meier (2000), Feola (2014), Rudmin (1990), Leisinger (1998), Leipämaa-Leskinen et al (2016), Friedman andFriedman (2010), Whitney Sanford (2013), Kannisto (2018), Van Steenbergen and Feller (1979), Nefat (2016), Alexander (2014, Fraňková and Johanisová (2013), Kaynak and Eksi (2013), Hellöre (2008), Little (1995), Williams (1984) Quantitative studies Surveys 31 Kuanr et al (2020), Peifer et al (2020, Lee (2019), Balderjahn and Hüttel (2019), Taljaard and Sonnenberg (2019), Kropfeld et al (2018), Bayat and Sezer (2018), Chowdhury (2018), …”
Section: Research Methods Data Collection Technique Articles Referencesmentioning
confidence: 99%
“…Despite the prevalence of materialism in society, some consumers purposefully avoid highly materialistic lifestyles and shun excessive consumption. This group of consumers chooses to live a simpler life with fewer material possessions (Chowdhury, 2018; Peifer et al., 2019). Voluntary simplicity, which advocates singleness of purpose, sincerity and honesty within, as well as avoidance of exterior clutter, of many possessions irrelevant to the chief purpose of life, is a phrase coined by Gregg (1936, p. 6), and then, elucidated by Elgin and Mitchell (1977).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Consumers’ desire to limit consumption and preference for sustainable consumption practices have become mainstream topics in the world of marketing, as more and more people try to limit their overall consumption and make responsible consumption decisions (Lee et al., 2016, 2018; White et al., 2019). Simple living has gained rising interest in several countries (e.g., Hüttel et al., 2020; Peifer et al., 2019; Rich et al., 2020). A recent comprehensive review of the voluntary simplicity concept indicates that most studies in this area have used traditional research methods (Rebouças & Soares, 2020).…”
Section: Introductionmentioning
confidence: 99%